Scalable One-Pot Synthesis of Nitrogen and Boron Co-doped Few Layered Graphene by Submerged Liquid Plasma Exfoliation - Elumalai, Satheeshkumar; Su, Chia-Ying; Yoshimura, Masahiro (Frontiers in Materials, 2019)
We report a simple, one-pot solution-processing synthesize of nitrogen (N) and boron (B) co-doped in few-layered graphene by submerged liquid plasma exfoliation (SLPE) was developed. Simultaneous graphite exfoliation and N, and B co-doping in few layered graphene nanosheets (NB-GNs) were produced by micro-plasma discharge at the graphite tip immersed in the acetonitrile (ACN) solvent containing sodium tetraphenylborate. Higher boron contents led to an amorphous nano-carbon, while a few-layered NB-GNs was obtained at low boron content in the ACN reaction mixture. To analyze the structural defect, nanosheets morphology, N and B co-doping in few-layered graphene, X-ray diffraction (XRD), Raman spectroscopy, transmission electron microscopy coupled with energy-dispersive X-ray spectroscopy (TEM-EDS) and X-ray photoelectron spectroscopy (XPS) were used. This solution-processing strategy will be useful for the practical option of exploring a large family of two-dimensional (2D) materials.